Oxidative Stress-Induced Ferroptosis in Cardiovascular Diseases and Epigenetic Mechanisms - Li, Jiamin; Zhou, Yunxiang; Wang, Hui; Lou, Jianyao; Lenahan, Cameron; Gao, Shiqi; Wang, Xiaoyu; Deng, Yongchuan; Chen, Han; Shao, Anwen (Frontiers in Cell and Developmental Biology, 2021)
The recently discovered ferroptosis is a new kind of iron-regulated cell death that differs from apoptosis and necrosis. Ferroptosis can be induced by an oxidative stress response, a crucial pathological process implicated in cardiovascular diseases. Accordingly, mounting evidence shows that oxidative stress-induced ferroptosis plays a pivotal role in angio-cardiopathy. To date, the inhibitors and activators of ferroptosis, as well as the many involved signaling pathways, have been widely explored. Among which, epigenetic regulators, molecules that modify the package of DNA without altering the genome, emerge as a highly targeted, effective option to modify the signaling pathway of ferroptosis and oxidative stress, representing a novel and promising therapeutic potential target for cardiovascular diseases. In this review, we will briefly summarize the mechanisms of ferroptosis, as well as the role that ferroptosis plays in various cardiovascular diseases. We will also expound the epigenetic regulators of oxidative stress-induced ferroptosis, and the promise that these molecules hold for treating the intractable cardiovascular diseases.